Knockdown of Lamin B1 and the Corresponding Lamin B Receptor Leads to Changes in Heterochromatin State and Senescence Induction in Malignant Melanoma - Lämmerhirt, Lisa; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Pommer, Michaela; Zimmermann, Tom; Kluge, Viola; Matthies, Alexander Oliver; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2022)
Modifications in nuclear structures of cells are implicated in several diseases including cancer. They result in changes in nuclear activity, structural dynamics and cell signalling. However, the role of the nuclear lamina and related proteins in malignant melanoma is still unknown. Its molecular characterisation might lead to a deeper understanding and the development of new therapy approaches. In this study, we analysed the functional effects of dysregulated nuclear lamin B1 (LMNB1) and its nuclear receptor (LBR). According to their cellular localisation and function, we revealed that these genes are crucially involved in nuclear processes like chromatin organisation. RNA sequencing and differential gene expression analysis after knockdown of LMNB1 and LBR revealed their implication in important cellular processes driving ER stress leading to senescence and changes in chromatin state, which were also experimentally validated. We determined that melanoma cells need both molecules independently to prevent senescence. Hence, downregulation of both molecules in a BRAFV600E melanocytic senescence model as well as in etoposide-treated melanoma cells indicates both as potential senescence markers in melanoma. Our findings suggest that LMNB1 and LBR influence senescence and affect nuclear processes like chromatin condensation and thus are functionally relevant for melanoma progression.
CRIS-Team Scopus Importer:2022-08-05
Keywords: chromatin state; heterochromatin foci; LBR; LMNB1; melanoma; nuclear lamina; senescence

Learning from Embryogenesis-A Comparative Expression Analysis in Melanoblast Differentiation and Tumorigenesis Reveals miRNAs Driving Melanoma Development - Linck-Paulus, Lisa; Lämmerhirt, Lisa; Voeller, Daniel; Meyer, Katharina; Engelmann, Julia C.; Spang, Rainer; Eichner, Norbert; Meister, Gunter; Kuphal, Silke; Boßerhoff, Anja Katrin (Journal of Clinical Medicine, 2021)
Malignant melanoma is one of the most dangerous tumor types due to its high metastasis rates and a steadily increasing incidence. During tumorigenesis, the molecular processes of embryonic development, exemplified by epithelial-mesenchymal transition (EMT), are often reactivated. For melanoma development, the exact molecular differences between melanoblasts, melanocytes, and melanoma cells are not completely understood. In this study, we aimed to identify microRNAs (miRNAs) that promote melanoma tumorigenesis and progression, based on an in vitro model of normal human epidermal melanocyte (NHEM) de-differentiation into melanoblast-like cells (MBrCs). Using miRNA-sequencing and differential expression analysis, we demonstrated in this study that a majority of miRNAs have an almost equal expression level in NHEMs and MBrCs but are significantly differentially regulated in primary tumor- and metastasis-derived melanoma cell lines. Further, a target gene analysis of strongly regulated but functionally unknown miRNAs yielded the implication of those miRNAs in many important cellular pathways driving malignancy. We hypothesize that many of the miRNAs discovered in our study are key drivers of melanoma development as they account for the tumorigenic potential that differentiates melanoma cells from proliferating or migrating embryonic cells.
CRIS-Team WoS Importer:2021-06-25

Loss of miR-101-3p in melanoma stabilizes genomic integrity, leading to cell death prevention - Lämmerhirt, Lisa; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Meier, Paula; Stäbler, Sebastian; Kuphal, Silke; Boßerhoff, Anja Katrin (Cellular & Molecular Biology Letters, 2024)
Malignant melanoma remains the most lethal form of skin cancer, exhibiting poor prognosis after forming distant metastasis. Owing to their potential tumor-suppressive properties by regulating oncogenes and tumor suppressor genes, microRNAs are important player in melanoma development and progression. We defined the loss of miR-101-3p expression in melanoma cells compared with melanocytes and melanoblast-related cells as an early event in tumor development and aimed to understand the tumor suppressive role of miR-101-3p and its regulation of important cellular processes. Reexpression of miR-101-3p resulted in inhibition of proliferation, increase in DNA damage, and induction of apoptosis. We further determined the nuclear structure protein Lamin B1, which influences nuclear processes and heterochromatin structure, ATRX, CASP3, and PARP as an important direct target of miR-101-3p. RNA sequencing and differential gene expression analysis after miR-101-3p reexpression supported our findings and the importance of loss of mir-101-3p for melanoma progression. The validated functional effects are related to genomic instability, as recent studies suggest miRNAs plays a key role in mediating this cellular process. Therefore, we concluded that miR-101-3p reexpression increases the genomic instability, leading to irreversible DNA damage, which leads to apoptosis induction. Our findings suggest that the loss of miR-101-3p in melanoma serves as an early event in melanoma progression by influencing the genomic integrity to maintain the increased bioenergetic demand.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Apoptosis; DNA damage; Genomic integrity; Melanoma; miR-101-3p; miRNA; RNA-seq

Molecular changes induced in melanoma by cell culturing in 3D alginate hydrogels - Kappelmann-Fenzl, M.; Schmidt, Sonja; Fischer, Stefan; Schmid, Rafael; Lämmerhirt, Lisa; Fischer, Lena; Schrüfer, Stefan; Thievessen, Ingo; Schubert, Dirk W.; Matthies, Alexander Oliver; Detsch, Rainer; Boccaccini, Aldo R.; et al. (Cancers, 2021)
Alginate hydrogels have been used as a biomaterial for 3D culturing for several years. Here, gene expression patterns in melanoma cells cultivated in 3D alginate are compared to 2D cultures. It is well-known that 2D cell culture is not resembling the complex in vivo situation well. However, the use of very intricate 3D models does not allow performing high-throughput screening and analysis is highly complex. 3D cell culture strategies in hydrogels will better mimic the in vivo situation while they maintain feasibility for large-scale analysis. As alginate is an easy-to-use material and due to its favorable properties, it is commonly applied as a bioink component in the growing field of cell encapsulation and biofabrication. Yet, only a little information about the transcriptome in 3D cultures in hydrogels like alginate is available. In this study, changes in the transcriptome based on RNA-Seq data by cultivating melanoma cells in 3D alginate are analyzed and reveal marked changes compared to cells cultured on usual 2D tissue culture plastic. Deregulated genes represent valuable cues to signaling pathways and molecules affected by the culture method. Using this as a model system for tumor cell plasticity and heterogeneity, EGR1 is determined to play an important role in melanoma progression.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D cultivation; Biomaterials; EGR1; Melanoma; Whole transcriptome

The Nuclear Envelope Proteins LMNB1 and LBR influence the Chromatin Structure and Senescence Processes in Melanoma - Lämmerhirt, Lisa; Pommer, Michaela; Zimmermann, Tom; Kluge, Viola; Kuphal, Silke; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23